A SUPPORTIVE LEARNING ENVIRONMENT, THE CREATION OF IT AS AN EDUCATIONAL FACTOR: AN ANALYSIS OF TEACHERS’ AND STUDENTS’ ATTITUDE - Jatkauskienė Birutė; Andriekienė, Rūta Marija; Nugaras, Modestas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
This article presents a study, an analysis of teachers’ and students’ attitude toward the concept of a learning environment, elements of the development of it, the accountability for creating a supportive learning environment, by revealing an educational effect of it on student relationships and on outcomes of studies and learning. The research is aimed to answer the main problematic question: how do teachers and students perceive a learning environment, its elements, the creation, accountability for a supportive learning environment, what kind of educational effect may it have? The article consists of an introduction, study design, research results, conclusions, and references. The empirical study shows that teachers and students have quite a clear understanding of the concept of a learning environment, however, both groups under study (teachers and students) construe various learning environments, elements of their creation, accountability of actors for creating and maintaining the environments in a different way. In spite of some differences in attitudes of teachers and students, both groups of respondents acknowledge the fact that a learning environment has an educational effect on interrelationships of students, outcomes of learning and studies. It has to be assumed that observations made in this research can be used in the teaching practice so as to better understand contemporary students, relationships between teachers and students, as well as the formation of students’ positive attitudes toward learning activities and communication.